Textural and chemical properties of carbon xerogels for the catalytic wet air oxidation of aniline - Machado, Bruno (2010)
Previous works reporting the use of carbon materials in the oxidative treatment of aromatic compounds and of nitrogen containing compounds seem to indicate that their catalytic activity is intimately related to their surface chemistry and porous texture [1- 3]. In this work we prepared a mesoporous carbon xerogel (CX) material with a significant amount of oxygen functional groups and tested it in the Catalytic Wet Air Oxidation (CWAO) of aqueous aniline solutions. A commercial activated carbon (ROX, from Norit) was used as standard for comparison purposes. The results will have predictive value in establishing relationships between structure and catalyst efficiency in CWAO.